2012
DOI: 10.1071/rd11195
|View full text |Cite
|
Sign up to set email alerts
|

Levels of mRNA for bone morphogenetic proteins, their receptors and SMADs in goat ovarian follicles grown in vivo and in vitro

Abstract: This study investigated the stability of housekeeping genes (glyceraldehyde-3-phosphate dehydrogenase, β-tubulin, β-actin, phosphoglycerate kinase (PGK), 18S rRNA, ubiquitin and ribosomal protein 19) and the levels of mRNA for bone morphogenetic protein-2 (BMP-2), -4 (BMP-4), -6 (BMP-6), -7 (BMP-7) and -15 (BMP-15), their receptors (BMPR-IA, -IB and -II) and Similar to Mothers Against Decapentaplegic (SMADs) (-1, -5 and -8) in goat follicles of 0.2, 0.5 and 1.0mm, as well as in secondary follicles before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…() and Costa et al. () observed similar results, showing the down‐regulation of BMPR1A and BMPR2 expression after in vitro culture of ovine granulosa cells and caprine secondary follicles, respectively. Previous studies demonstrated that BMP‐6 plays a role in follicular development through the proliferation and differentiation of granulosa cells (Juengel et al.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…() and Costa et al. () observed similar results, showing the down‐regulation of BMPR1A and BMPR2 expression after in vitro culture of ovine granulosa cells and caprine secondary follicles, respectively. Previous studies demonstrated that BMP‐6 plays a role in follicular development through the proliferation and differentiation of granulosa cells (Juengel et al.…”
Section: Discussionmentioning
confidence: 57%
“…The results of a recent study showed that the mRNA expression for BMP6 gene increases with in vivo follicular growth from primordial to secondary follicle stage (Costa et al. ), indicating the importance of BMP‐6 during the follicular growth in goats. Moreover, the protein and mRNA expression of BMP6 was demonstrated in the caprine oocytes of follicles during all stages of development, particularly in those from antral follicles (Frota et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Follicle culture at different stages of development has been used to study diverse biological processes (folliculogenesis, steroidogenesis, and oocyte maturation) in various species, such as goat [9,10], mouse [11][12][13], rat [14], sheep [15,16], dog [17][18][19], and monkey [20][21][22][23]. Regarding the domestic cat, efforts to date have focused on oocytes [7,[24][25][26][27][28][29][30] or preantral follicle cultures [19,31].…”
Section: Introductionmentioning
confidence: 99%